To bird flight. Birds in the archaeological, ethnographic and ethnohistorical record of the Mendoza and San Juan (Argentine Central West) - Chiavazza, Horacio; Guardia, Nicolás; Prieto-Olavarría, Cristina (Facultad de Filosofía y Humanidades. Museo de Antropología, 2023)
Although there are mentions in ethnohistoric, ethnographic and archaeological works, the role that birds had in human life in the Central West of Argentina has not been considered, with few exceptions. From the survey of archaeological, historical and ethnographic information, it is evident that, in a long history, in the various social and cultural contexts that developed in the area, birds did not limit their contribution to subsistence, but participated within systems of visual representation that suppose iconographies and uses derived from belief systems, rituals and symbols of power. It is proposed that the presence of birds was constant and significant in archaeological contexts and was not limited only to osteoarchaeological evidence, since it is represented in a wide variety of supports, in addition to its mention in ethnographic and documentary accounts. From this perspective, it is proposed that it is a registry that should be inserted with greater emphasis in the future research agenda in the region.